Comparison Of Non-Surgical Managements Versus Surgical Managements Of Chronic Anal Fissure - Gita Prinita; Andre Setiawan Suryadi; Teinny Suryadi (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
ABSTRACT Anal fissure is a tear of the anoderm distal to the dentate line and is very common in all age groups, with an equal incidence in males and females. Most acute anal fissures heal without surgical intervention but chronic anal fissures are usually more difficult to treat due to recurrence and complications. In addition, chronic anal fissures also have a negative impact on quality of life. Management of anal fissures consists of non-surgical and surgical where the healing rate of chronic anal fissures is higher with surgical management. However, surgery carries a risk of incontinence. This article discusses the comparison of the results of non-surgical management with surgical management of chronic anal fissures. Â